Algebra model and experiment for semantic link network. (3rd January 2006) - Zhuge, Hai; Sun, Yunchuan; Jia, Ruixiang; Liu, Jie
Semantic Link Network, SLN, is a semantic extension of hyperlink network. Based on the previous SLN model, this paper enriches the semantic links and reasoning rules, proposes an algebra model that supports semantic reasoning and the management of SLN by using a semantic matrix and presents the experiment for putting an SLN into practice. A solution to efficiently manage a huge SLN by dividing the whole SLN into partitioned semantic matrices is also put forth. The consistency issue about SLN is discussed, based on the matrix representation. Experiment of establishing and using the SLN shows the feasibility of the proposed model.